Clinical case of the postinfarction ventricular septum defect successful closure with occluder at the 4th day of the disease - B.М. Todurov; М.F. Rotar; А.V. Khokhlov; К.S. Boiko; Yu.V. Hutsuliak (Кардіохірургія та інтервенційна кардіологія)
The search of effective treatment of myocardial infarction complications remains a relevant issue. Despite the constant improvement of techniques and methods of surgical interventions and the improvement of medical treatment protocols, the mortality due to the postinfarction rupture of the interventricular septum remains quite high. The article presents a clinical case of successful endovascular closure of a postinfarction ventricular septum defect with an occluder with its subsequent surgical closure. The optimal timing of the intervention, the choice of the type of intervention, the optimal medical and hemodynamic support at the stage of preparing the patient for the correction of this complication and in the early postoperative period are described. Our experience shows that the timely use of endovascular techniques to close the defect allows you to create a bridge for open surgery and provide an effective treatment.